Androgen receptor in bladder cancer: A promising therapeutic target - Abhishek Tripathi; Shilpa Gupta (Asian Journal of Urology)
There has been a significant progress in the treatment of metastatic urothelial carcinoma in the last few years with the advent of immunotherapy after a long gap of no drug approvals for over 4 decades. While immunotherapy with checkpoint inhibitors has revolutionized the treatment of urothelial carcinoma, unfortunately, only a minority of patients respond to immunotherapy. Treatment options for patients who do not respond and/or progress on immunotherapy are very limited and overall prognosis remains dismal in metastatic urothelial carcinoma. The first targeted therapy targeting the fibroblast growth factor receptor (FGFR) was recently approved for bladder cancer, but it is effective only in select patients harboring the FGFR2 and FGFR 3 mutations. Antibody drug conjugates like enfortumab vedotin have shown promising activity in clinical trials. Development of novel targeted therapies remains an area of investigation and an unmet need in bladder cancer. Exploitation of androgen receptor (AR) is a potential strategy for targeted drug development in bladder cancer. A significant proportion of urothelial carcinoma patients express AR irrespective of gender. AR signaling in urothelial carcinoma has been linked to progression through multiple mechanisms, including activation of human epidermal growth factor receptor-2 (EGFR or HER-2) signaling and epithelial to mesenchymal transition (EMT). Furthermore, AR is enriched in the luminal papillary mRNA subtype of urothelial carcinoma and also mediates resistance to cisplatin-based chemotherapy. Preclinical evidence suggests that AR inhibition can successfully inhibit urothelial carcinoma growth as monotherapy and is synergistic with cisplatin-based chemotherapy. We review the preclinical and clinical evidence supporting the putative role of AR signaling in urothelial carcinoma pathogenesis, progression and its role as a novel therapeutic target and future directions.